Laboratory Microprobe X-Ray Fluorescence in Plant Science: Emerging Applications and Case Studies - Rodrigues, Eduardo S.; Gomes, Marcos H. F.; Duran, Nádia M.; Cassanji, João G. B.; da Cruz, Tatiana N. M.; Sant’Anna Neto, Analder; Savassa, Susilaine M.; de Almeida, Eduardo; Carvalho, Hudson W. P. (Frontiers in Plant Science, 2018)
In vivo and micro chemical analytical methods have the potential to improve our understanding of plant metabolism and development. Benchtop microprobe X-ray fluorescence spectroscopy (μ-XRF) presents a huge potential for facing this challenge. Excitation beams of 30 μm and 1 mm in diameter were employed to address questions in seed technology, phytopathology, plant physiology and bioremediation. Different elements were analyzed in several situations of agronomic interest: (i) Examples of µ-XRF yielding quantitative maps that reveal the spatial distribution of zinc in common beans (Phaseolus vulgaris) primed seeds. (ii) Chemical images daily recorded at a soybean leaf (Glycine max) infected by anthracnose showed that phosphorus, sulfur and calcium trended to concentrate in the disease spot. (iii) In vivo measurements at the stem of Phaseolus vulgaris showed that under root exposure, manganese is absorbed and transported nearly 10-fold faster than iron. (iv) Quantitative maps showed that the lead distribution in a leaf of Eucalyptus hybrid was not homogenous, this element accumulated mainly in the leaf border and midrib, the lead hotspots reached up to 13,400 mg lead kg-1 fresh tissue weight. These case studies highlight the ability of µ-XRF regards in performing qualitative and quantitative elemental analysis of fresh and living plant tissues. Thus, it can probe dynamic biological phenomena non-destructively and in real time.